ANALISIS SERAPAN ANGGARAN SEBAGAI PENGUKURAN KINERJA KEUANGAN DAN DAMPAKNYA BAGI TINGKAT KESEJAHTERAAN MASYARAKAT KABUPATEN TEMANGGUNG - Nuwun Priyono; Maya Maghfiroh; Chaidir Iswanaji (Jurnal Akuntansi dan Pajak, 2022)
This research has the aim of determining the absorption of the budget as a measurement of the performance of the Regional Government, the supporting and inhibiting factors of budget absorption in the local government and to determine its impact on improving the welfare of the people in Temanggung Regency for the 2013-2017 period. This research is a qualitative research, using secondary data sources in the form of Budget Realization Report (LRA) and primary data in the form of interviews regarding the supporting and inhibiting factors of budget absorption. The data analysis technique was carried out using a qualitative descriptive method. The results showed that the performance ability of the Temanggung Regency Government in managing and exploring local revenue sources in 2013-2017 was good with the absorption of the revenue budget showing an average number of 99.79%. The ability of the local government of Temanggung Regency to use the budget in 2013-2017 is not good, as can be seen from the absorption of the expenditure budget which shows an average figure of 89.2%. The supporting factors for budget absorption in the Temanggung Regency Regional Government were: timeliness in reporting income, orderly administrative management, and the integrity of the revenue manager. The inhibiting factors for budget absorption in the Temanggung Regency Regional Government were: budget planning, implementation of activities, the auction process (tander), and position transfers. Then the amount of increase or decrease in the absorption of the revenue and expenditure budget can have an impact on the level of welfare which can be seen from the achievement of the HDI value in Temanggung Regency. Keywords: Budget Absorption, Causative, Supporting, Welfare